2017
DOI: 10.17269/cjph.108.5878
|View full text |Cite
|
Sign up to set email alerts
|

Cybervictimization among preadolescents in a community-based sample in Canada: Prevalence and predictors

Abstract: OBJECTIVES: To examine the prevalence and predictors associated with cybervictimization among preadolescents in a community-based sample from Canada.METHODS: Data were drawn from a cohort of 5783 students of grades 5-8, aged 9-14 from 109 elementary schools at the Saskatoon Health Region, Saskatchewan of Canada based on the Student Health Survey in the year of 2010-2011. Multivariate logistic regression with the generalized estimating equation was used to determine the individual and contextual factors associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…The results of the analyzed studies on abuse, neglect, rejection, poor relationships, and family dysfunctions (Bjereld et al 2017;Chen et al 2018;Hong et al 2018;Mobin et al 2017;Stavrinides et al 2018) achieved a significant level of agreement in their positive relationship with the involvement in cybervictimization. The findings of these studies on poor parent-child relationships are similar to previous outcomes (e.g., Gomes-Franco-Silva and Sendín-Gutiérrez 2014; Lereya et al 2013).…”
Section: Poor Parent-child Relationshipsmentioning
confidence: 86%
See 2 more Smart Citations
“…The results of the analyzed studies on abuse, neglect, rejection, poor relationships, and family dysfunctions (Bjereld et al 2017;Chen et al 2018;Hong et al 2018;Mobin et al 2017;Stavrinides et al 2018) achieved a significant level of agreement in their positive relationship with the involvement in cybervictimization. The findings of these studies on poor parent-child relationships are similar to previous outcomes (e.g., Gomes-Franco-Silva and Sendín-Gutiérrez 2014; Lereya et al 2013).…”
Section: Poor Parent-child Relationshipsmentioning
confidence: 86%
“…Finally, Bjereld et al (2017) concluded that cyberbullied children had poorer relationships with their parents. Similarly, the findings of Mobin et al (2017) suggested that children who had a poor relationship with their parents were more likely to be cybervictims.…”
Section: Parental Educational Stylesmentioning
confidence: 95%
See 1 more Smart Citation
“…Self-esteem is a feeling towards oneself depending on its characteristics and can be positive or negative [38]. In the last years, the number of studies based on the relation between cybervictimization and self-esteem in adolescents has increased [39][40][41][42]. Additionally, it has been observed that cybervictimization has a negative connection with self-esteem [39,40,43].…”
Section: Cyberbullying and Self-esteemmentioning
confidence: 99%
“…In the last years, the number of studies based on the relation between cybervictimization and self-esteem in adolescents has increased [39][40][41][42]. Additionally, it has been observed that cybervictimization has a negative connection with self-esteem [39,40,43]. Cybervictims show lower levels of self-esteem, sense of belonging to school and commitment with it [42], fact that is more accentuated in girls than in boys [17].…”
Section: Cyberbullying and Self-esteemmentioning
confidence: 99%